Depositional environment and petroleum source rock potential of Mesozoic lacustrine sedimentary rocks in central Mongolia. (June 2022) - Erdenetsogt, Bat-Orshikh; Hong, Sung Kyung; Choi, Jiyoung; Lee, Insung
Abstract: Middle Jurassic (five samples from one location) and Lower Cretaceous (thirty-two samples from eight locations) lacustrine sedimentary rocks of central Mongolia were studied to determine their depositional environments and petroleum source rock potential. The Middle Jurassic shale contains sufficient organic matter (OM) with Type II/III kerogen to represent a mixed oil and gas potential source rock. Tmax and biomarker maturity indices suggest a thermally immature level. Pristane/phytane and the gammacerane index indicate that the shale accumulated in an oxic, freshwater environment. Terrigenous OM with input from algae and macrophytes was a major contributor as indicated by long-chain n -alkanes and the abundance of C29 regular steranes. The stable carbon and nitrogen isotope compositions and kerogen types agree with land plant derived OM. Lower Cretaceous shales are highly oil-prone but thermally immature, reflected by Rock-Eval data and biomarker parameters. Carbon preference index (CPI), n- alkane distributions, and C27/ C29 ratios suggest that OM in Lower Cretaceous shales is a mixture of phytoplankton, macrophyte, and land plant. The contribution from algal OM is variable. Lower Cretaceous shales were deposited in stratified lakes with anoxic bottom waters and the salinity of paleolakes was variable, indicated by Pr/Ph and the gammacerane index, respectively. Organic geochemical characteristics and depositional environments of Middle Jurassic and Lower Cretaceous sedimentary rocks studied herein are similar to those of Jurassic source rocks in western Chinese basins and Lower Cretaceous source rocks in eastern Mongolian basins, respectively. Highlights: Geochemical characteristics and depositional environments of Mesozoic lacustrine shales in Central Mongolia are studied. The lacustrine shales share many similarities to the source rocks in western Chinese and eastern Mongolian basins. The lacustrine sedimentary rocks have promising petroleum source rock potential. Central Mongolian basins hosting Mesozoic source rocks are viable targets for hydrocarbon exploration.